Fatal gastrointestinal bleeding associated with acute pancreatitis as a complication of Covid-19: a case report. Issue 5 (May 2022) - Mitrovic, Milica; Tadic, Boris; Jankovic, Aleksandra; Rankovic, Ivan; Kovac, Jelena Djokic
Clinical manifestations of Covid-19 vary widely among patients. Recent studies suggest that up to 15% of patients with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infections develop gastrointestinal symptoms. The location of virus–host cell receptors angiotensin-converting enzyme 2 and transmembrane serine protease 2 has an important role in the pathophysiology and presentation of disease. They are expressed in the respiratory tract, as well as other organs and tissues including exocrine and endocrine pancreatic cells. These cells are therefore a possible target for the virus, which could explain the relationship between SARS-CoV-2 infection and pancreatic injury. We report a disastrous collateral effect of the Covid-19 pandemic on a 33-year-old man with chronic renal insufficiency and asymptomatic SARS-CoV-2 infection, who developed acute pancreatitis. Inflammation progressed rapidly toward necrosis and the development of a peripancreatic pseudoaneurysm which subsequently ruptured, causing death.